Curing Reaction and Dielectric Properties of Rigid and Elastic Liquid Crystal Epoxy Networks Modified with Nanofillers - Magdalena Włodarska (International Journal of Polymer Science)
The aim of the paper is to compare the progress of the curing reaction and the dielectric properties of liquid crystalline epoxy networks of different elasticity and to investigate how modification with nanofillers influences their properties. The study focuses on a liquid crystalline epoxy monomer with four aromatic rings in the mesogen, cross-linked with 4,4′-diaminodiphenylmethane (DDM) and pimelic acid (PA) to produce rigid and elastic polymer networks. The obtained results are compared to networks modified with nanofillers (diphenyl aluminum phosphate nanorods). The curing process is monitored in situ with broadband dielectric spectroscopy, which is a good tool to view the progress of the reaction. Two stages with different reaction dynamics are observed in the studied cases. Dielectric properties of the products cured with two chosen agents show significant differences in the obtained parameters (activation energy, glass transition, and fragility index) as well as in the dynamics of the α and β relaxations. Although the curing agent is the main factor determining the properties of the product, the nanofiller additive also modifies the values of specific parameters that characterize both the process of the reaction and the properties of the final composites. Particularly, adding the nanofiller raises the glass transition temperature in both the cases. The obtained results are in good agreement with the earlier calorimetric study.